2015
DOI: 10.3357/amhp.3244.2015
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Operations Evaluation for Using Remote-Guidance Ultrasound for Exploration Spaceflight

Abstract: RG produces US images of higher quality than those produced with only computer-based instruction. Extended communication delays in exploration missions will eliminate the option of real-time guidance, thus requiring autonomous operation. The computer program used appears effective and could be a model for future digital US expertise banks. Terrestrially, it also provides adequate self-training and mentoring mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…These practice sessions included mock data collection for each image to be captured. During spaceflight the astronauts acquired carotid and brachial artery images with remote guidance, a technique in which astronauts received near-real-time instruction regarding ultrasound probe placement, image quality, and equipment operation (39). Sonographers viewed video from the ultrasound and from a camera on ISS that showed the location and orientation of the ultrasound probe.…”
Section: Methodsmentioning
confidence: 99%
“…These practice sessions included mock data collection for each image to be captured. During spaceflight the astronauts acquired carotid and brachial artery images with remote guidance, a technique in which astronauts received near-real-time instruction regarding ultrasound probe placement, image quality, and equipment operation (39). Sonographers viewed video from the ultrasound and from a camera on ISS that showed the location and orientation of the ultrasound probe.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the individuals evaluated, one study evaluated emergency medicine residents with one to two years of previous experience with ultrasound, 4 and two studies evaluated medical students. 2 , 6 The other seven studies, conducted in Canada, South Korea, the United States and Haiti, evaluated non-medical professionals: 1 , 29 34 six studies on other healthcare professionals 1 , 29 31 , 33 , 34 (including sonographers and nurses) and one study on firefighters. 32 All of these ten studies featured a trained and experienced physician as a distant assessor.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized clinical trial by Hurst et al, 33 30 sonographers with no previous experience were evaluated. These were divided into three groups: 10 who had had a computer class (two-minute videos); 10 who had had a computer class (two-minute videos) plus telementoring; and 10 who had only had telementoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject also watched a medical video demonstrating a person performing self-ultrasound 15 . It was shown that both remote guidance and a computer training tool produce a higher quality of ultrasound images 6,9 . During the procedure, the subject performed the test while guided remotely by the sonographer, who was in a separate location from the subject.…”
Section: Experiments Designmentioning
confidence: 99%